Розрахунок кутової залежності випромінювання, що розсіяне поверхнею фотопружного середовища - Semchuk, O. Yu.; Klymenko, V. E. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
The angular dependence of irradiation scattering by surface of photoelastic media is calculated within the framework of the theory of noncoherent scattering caused by the interaction of electromagnetic wave with fluctuations of Rayleigh surface waves. The analysis of integral scattering factor demonstrates that the heterogeneity of permittivity gives an essential input to value of the former at scattering angles up to 35°. With the further increase in scattering angle, the photoelastic mechanism of scattering becomes already decisive.